Simultaneous Coronary Artery Bypass Grafting and Anterior Rectum Resection: The First Clinical Case in Kazakhstan - Anuar Abdikarimov; Serik Aitaliyev; Vladimir Dikolayev (Acta Medica Lituanica)
In this case report, we describe the experience of a patient who was initially admitted for rectal cancer treatment. However, during the preoperative evaluation, severe stenosis of the coronary arteries was unexpectedly detected, presenting the medical team with a complex decision-making process.